Naqsh-i anbiyā' va payāmbarān dar hidāyat va 'adālat - Bihishtī, Muhammad, . 1982 (Sitād-i Bar'guzārī-i Marāsim-i Haftum-i Tīr : Markaz-i pakhsh : Daftar-i Markazī-i Hizb-i Jumhūrī-i Islāmī, 1983)
Chiefly on the background and significance of the 1979 Islamic revolution in Iran; lectures by an eminent religious scholar from Iran.